The Influence of Social Media Marketing, Celebrity Endorsement, and Electronic Word of Mouth (E-WOM) on Consumer Purchase Intention : (A Case Study of Mustika Ratu Beauty Products in Semarang, Indonesia) - Anggun Mutiarasari; Ariyantiano Bagus Muchamat Isnain; Intan Amalina Zulfa; Grace’tia Erich Nugraheni (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study examines the impact of Social Media Marketing, Celebrity Endorsement, and Electronic Word of Mouth (E-WOM) on consumer purchase intention for Mustika Ratu beauty products in Semarang, Indonesia. The research employs a quantitative approach, with 97 respondents selected through purposive sampling. Data were collected via structured questionnaires, and the analysis was conducted using multiple linear regression, t-tests, F-tests, and the coefficient of determination in SPSS. The results indicate that Social Media Marketing and E-WOM both have a positive and significant impact on consumer purchase intention. In contrast, Celebrity Endorsement was found to have a negative and insignificant effect on purchase intention. When considered simultaneously, all three variables significantly influence consumer purchase intention. These findings highlight the increasing role of digital engagement, particularly through social media platforms and online peer reviews, in shaping consumer behavior in the beauty industry. The study also points out that, despite the popularity of celebrity endorsements, their influence on purchasing decisions may not always be as impactful as digital marketing strategies and E-WOM, which appear to resonate more strongly with consumers. Additionally, the research provides valuable insights into the digital marketing strategies in the Indonesian beauty sector, particularly how local beauty brands like Mustika Ratu can leverage social media and online word-of-mouth to strengthen their market positioning. This study offers practical recommendations for businesses aiming to improve their marketing strategies by focusing on online engagement and consumer feedback, which are critical in today’s highly competitive and digitally-driven consumer environment. The findings contribute to the broader literature on the effectiveness of digital marketing in the Indonesian market and suggest potential areas for further research into consumer behavior in the beauty industry.